2019
DOI: 10.1051/bioconf/20191201017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological characterization of the grapevine cultivars “Italia” in the Ica and Cañete valleys (Peru)

Abstract: The denomination of “Uva de Italia” or “Italia” is commonly used by growers to refer to a group of varieties used from the colonial times to making a brandy of Pisco with muscat aroma. Previous work have demonstrated that Uva de Italia corresponds in fact to the variety Muscat of Alexandria, a widely spread variety around the world and in South America. However, the distinction between “Italia Dorada” and “Italia Rosada” is usually made, in allusion to the color variations observed in the berries. Our aim was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Many years later, molecular studies characterising the genetic origin of some of the most known criollas (e.g. Torrontés Riojano) appeared (Agüero et al 2003, Martínez et al 2006, Milla‐Tapia et al 2007), and a renewed interest has been observed lately in different countries (Aliquó et al 2017, Mendoza et al 2019). Recent evidence exploring the germplasm collection of the Instituto Nacional de Tecnología Agropecuaria (INTA) in Mendoza, showed that the diversity within the group of criollas is higher than previously thought (Aliquó et al 2017), and suggests that further diversity may be found in ancient vineyards.…”
Section: Introductionmentioning
confidence: 99%
“…Many years later, molecular studies characterising the genetic origin of some of the most known criollas (e.g. Torrontés Riojano) appeared (Agüero et al 2003, Martínez et al 2006, Milla‐Tapia et al 2007), and a renewed interest has been observed lately in different countries (Aliquó et al 2017, Mendoza et al 2019). Recent evidence exploring the germplasm collection of the Instituto Nacional de Tecnología Agropecuaria (INTA) in Mendoza, showed that the diversity within the group of criollas is higher than previously thought (Aliquó et al 2017), and suggests that further diversity may be found in ancient vineyards.…”
Section: Introductionmentioning
confidence: 99%